2016
DOI: 10.3758/s13414-016-1182-8
|View full text |Cite
|
Sign up to set email alerts
|

Target object moderation of attentional orienting by gazes or arrows

Abstract: Recent studies have attempted to demonstrate the importance of the characteristics of directional cues and observers' traits in attentional orienting. This study investigated how attentional orienting is influenced by target processing. Two experiments showed the critical role played by target processing in attentional orienting that relies on eye-gaze and arrow cues. In Experiment 1, stronger attentional orienting was observed under the object-target condition compared with the scrambled-display condition, ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…These authors found qualitative differences in the fMRI data between gaze and arrow cues, but no differences in the behavioral data were found under the congruent and incongruent conditions. It is possible that the different influences of self-referential processing on the neural activity associated with attentional orienting under the incongruent and congruent conditions shown in the present study would have been more evident behaviorally if they had been assessed using a more difficult paradigm; indirect evidence supports this idea (e.g., Friesen et al, 2004 ; Sui et al, 2009 ; Yan et al, 2016 ). For example, using an identification task, Sui et al ( 2009 ) asked participants to identify whether a target at a left or right location was upright or inverted when using arrows after training trials were performed to associated the arrow cues with the words “self” and “friend”.…”
Section: Discussionmentioning
confidence: 58%
“…These authors found qualitative differences in the fMRI data between gaze and arrow cues, but no differences in the behavioral data were found under the congruent and incongruent conditions. It is possible that the different influences of self-referential processing on the neural activity associated with attentional orienting under the incongruent and congruent conditions shown in the present study would have been more evident behaviorally if they had been assessed using a more difficult paradigm; indirect evidence supports this idea (e.g., Friesen et al, 2004 ; Sui et al, 2009 ; Yan et al, 2016 ). For example, using an identification task, Sui et al ( 2009 ) asked participants to identify whether a target at a left or right location was upright or inverted when using arrows after training trials were performed to associated the arrow cues with the words “self” and “friend”.…”
Section: Discussionmentioning
confidence: 58%
“…Nevertheless, studies investigating related behaviors have found that attention to an arrow is stronger than attention to a face upon guidance. [ 34 ] Thus, attention may be a necessary factor in exploring the mechanism of facial processing in the future. In summary, the present study demonstrates that healthy adults have a specific processing pattern that is more likely based on configural analysis during face processing.…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 ] New evidence has shown that compared with healthy controls, schizophrenia patients exhibit a significant N170 latency sluggishness. [ 34 ] Because time-frequency (TF) analyses involve a 2-dimensional display mode to facilitate the observation of changes in the frequency components over time, TF analysis methods are frequently used to investigate nonstationary, nonlinear EEG signals. Since many brain functions are modulated by frequency specificity, many electrophysiological studies investigating face processing have focused on frequency oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the conclusions must be further confirmed with a larger sample size. In the future, we will design different experiments related to neurocognitive function ( 43 , 44 ) and use various analytical methods to explore the pathologic mechanisms of neurocognitive deficits in patients.…”
Section: Discussionmentioning
confidence: 99%